E-commerce 2023-2024: Business. Technology. Society. - Laudon, Kenneth C. (Pearson Education Limited, 2024)
The book provides an in-depth overview of e-commerce, focusing on core concepts and the latest practical data. The content is updated through September 2022 and includes examples from companies such as Meta, TikTok, Netflix, YouTube, Walmart, and Amazon, illustrating how e-commerce is transforming business operations and driving shifts in the global economy. Each chapter concludes with a section on careers in e-commerce, offering information on job opportunities and interview preparation guidance.